The Rate of Decline of Glomerular Filtration Rate May Not Be Associated with Polymorphism of the PPARγ2 Gene in Patients with Type 1 Diabetes and Nephropathy - Bingmei Yang; Hongxin Zhao; Beverley Ann Millward; Andrew Glen Demaine (PPAR Research)
The aim of the study was to investigate whether a Pro12Ala polymorphism in the peroxisome proliferator-activated receptor gamma 2 (PPARγ2) gene is associated with the progress of diabetic nephropathy in patients with type 1 diabetes. 197 Caucasian patients with type 1 diabetes and ethnically matched 151 normal healthy controls were genotyped for this polymorphism. Results showed that there were no significant differences in the frequencies of the genotypes and alleles of the polymorphism between groups. Multiple regression analysis in 77 patients demonstrated that the rate of decline in renal function in terms of glomerular filtration rate was significantly correlated to the baseline level of cholesterol (P=0.0014), mean diastolic blood pressure during follow-up period (P=0.019), and baseline level of HbA1c (P=0.022) adjusting for the effect of diabetes duration and gender, but no significant association was found between the polymorphism and the progression of diabetic nephropathy in our studied population. In summary, our results show that the PPARγ2 polymorphism is unlikely to be associated with the development and progression of the diabetic nephropathy in patients with type 1 diabetes. Further studies in different populations may be warranted to confirm our findings as the sample size in our study was relatively small.